60 Front Door Specialist Frailty MDT Working at MFT NHS Trust—The Therapy Team Poster Presentation. (16th March 2021) - Turner, H; Bennett, G; Hurst, S
Abstract: Introduction: The therapy team consists of physiotherapists, Occupational therapists and therapy technicians working generically to deliver a comprehensive therapy assessment to patients presenting in our Emergency Department, Clinical Decisions Unit and Medical Admissions Unit between the hours of 08:00–18:00 7 days a week. The therapists provide the hospitals frailty service in ED and MAU with early therapy assessment and intervention, supporting the provision of a Comprehensive Geriatric Assessment. The aims of our service are to provide early therapy assessment of our most vulnerable patients to avoid unnecessary hospital admissions and reduce readmission rates, and for those requiring hospital care to provide early mobilisation and discharge planning to reduce length of stay and complications associated with hospital admission. We provide the therapy component of the CGA as part of the specialist frailty MDT service and act as an interface with local community health and social services. Method: A full review of our frailty MDT service was undertaken and a re-allocation of our resources and staff was piloted in July 2019. During this pilot our therapy staff presence was re-distributed allowing greater patient numbers to be assessed promptly on their arrival to ED. This adjustment supported the Frailty MDT actions of: Further developing and redefining the Frailty nurse role basing them in ED and triage Close working relationships in ED between ED and frailty teams Education of ED staff in using the Clinical Frailty Score Releasing consultant geriatrician time, enabling them to be based in ED throughout the day Linking with community services Results: Data collection showed total referrals to therapy increased from 67 (June 2019) to 160 (July 2019). In July same day discharges were at 43%; discharges ≥72 hours 24%; 7 day readmission at 9%; 28 day readmissions at 11% and 38% were referred to community services. Conclusion: These changes enabled us to provide a full MDT frailty service to frail older people presenting at our ED in a timely manner and to a larger number of suitable patients.